Enhanced Radiation Shielding and Structural Modifications in Samarium (III) Oxide-Reinforced Type 316L Stainless Steel Composites for Nuclear Applications: A Comprehensive Evaluation of Physical, Structural, Mechanical, Gamma-Ray, and Neutron Attenuation Properties - Yayla, Nihal; Albayrak, M. Gokhan; Guler, Omer; Sen Baykal, Duygu; Alkarrani, Hessa; Almisned, Ghada; Tekin, H. O. (Taylor & Francis Inc, 2026)
Type 316L stainless steel (316L-SS) is widely recognized for its exceptional corrosion resistance, making it a preferred material in various industries. However, conventional stainless steel materials are inadequate for radiation shielding applications. While oxide dispersion-strengthened alloy composites with a 316L-SS matrix have been extensively studied in the literature for their mechanical creep properties, their radiation shielding capabilities remain insufficiently explored. This study investigates the potential of samarium oxide (Sm2O3) doped to improve the structural, physical, mechanical, and radiation shielding properties of 316L-SS composites. Samples containing 1%, 5%, 10%, and 20% Sm2O3 by weight were synthesized and extensively characterized using X-ray diffraction and scanning electron microscopy. These analyses revealed enhanced homogeneity and refined grain structure with increasing Sm2O3 content. Gamma-ray and neutron shielding properties demonstrated significant improvements, particularly in composites with 20% Sm2O3 reinforcement, as evidenced by lower half-value layer and mean free path values, along with an increased fast neutron removal cross section. However, a trade-off was observed between radiation shielding performance and mechanical properties: As the Sm2O3 content increased, the elastic modulus decreased, indicating reduced stiffness due to the incorporation of Sm2O3. This trade-off suggests that while Sm2O3 reinforcement effectively enhances radiation shielding, it may not be ideal for structural applications requiring high mechanical strength. Nevertheless, these findings highlight the potential of Sm2O3-doped 316L-SS composites for nonstructural radiation protection systems, particularly in applications where improved shielding performance is prioritized over mechanical stiffness.
Keywords: Samarium(III) oxide; Type 316 stainless steel; X-ray diffraction; scanning electron microscopy/energy dispersive spectroscopy; radiation shielding